The lost symbol : a novel - Brown, Dan, 1964- (New York : Doubleday, 2009)
Symbologist Robert Langdon returns in this new thriller follow-up to The Da Vinci Code.
Keywords: Cryptographers -- Fiction; Freemasonry -- Fiction; Washington (D.C.) -- Fiction; Suspense fiction; Adventure fiction